Agro-techniques for productivity enhancement in pea (Pisum sativum) at eastern Himalayan region - CHOUDHARY, V K; DIXIT, ANIL; BHAGAWATI, R (The Indian Journal of Agricultural Sciences, 2015)
Small scale experiments on pea (Pisum sativum L.) were designed during 2008 to 2011 at ICAR Research Complex for NEH Region, Basar, Arunachal Pradesh. The main objective of the study was to develop a suitable package of practices for the region to utilize the fallow land during post rainy season. Results confirmed that the minimum tillage registered 29.4% higher pod yield, while conventional tillage improved the length and dry biomass of root over no tillage. The seeds sown on 15 October registered 8.8-19.4% higher yields than the before and later sowing dates, but, line sown crop has obtained 18.2% higher pod yield over broadcasting. Planting geometry with 30 cm × 10 cm registered 5.4-21.4% higher pod yield. Phosphorus application at 75 kg/ha registered yield improvement of 2-32.3% and better utilization of irrigation water at 30 and 60 days after sowing (DAS) improved by 28.5% higher yield, in contrary, water use efficiency was improved by 9.7-15.3% with no irrigation. Hand weeding twice at 25 and 50 DAS recorded 9.5-39.6% higher yield over no weeding. Adoption of better package of practices in newer area under existing cropping system will play a key role in further yield improvement. Therefore, as per the availability of resources at site and feasibility, growers may use the practices to obtain higher pod yield in the region.